Deep Learning-Based Teacher Performance Management in Strengthening the Character of Graduate Profiles - Budiyanto Budiyanto; Mustaqim Mustaqim; Sukarman Sukarman (ARZUSIN, 2026)
The transformation of education through a deep learning approach requires madrasahs not only to pursue academic achievement but also to strengthen students’ character through meaningful learning experiences. In this context, co-curricular activities serve as a strategic medium for character development; however, their effectiveness depends substantially on the quality of teacher performance management. This study aims to analyze teacher performance management in the implementation of deep learning-based co-curricular activities to strengthen the character dimensions of the graduate profile at MTs Mathalibul Huda Mlonggo. A qualitative approach with a case study design was employed. Data were collected through interviews, observations, and document analysis and were analyzed using the interactive model of Miles, Huberman, and Saldaña, consisting of data condensation, data display, and conclusion drawing. The findings reveal that teacher performance management was implemented through three main stages: planning, implementation, and evaluation. During implementation, teachers functioned as facilitators, mentors, and learning companions by applying the principles of mindful learning, meaningful learning, and joyful learning. Evaluation was conducted through monitoring, supervision, reflection, and continuous improvement. Systematic teacher performance management contributed to strengthening the character dimensions of the graduate profile, particularly religiosity, integrity, responsibility, independence, collaboration, and leadership. The study concludes that deep learning-based co-curricular activities can serve as an effective instrument for character development when supported by structured and high-quality teacher performance management. These findings contribute to the discourse on madrasah-based character education and provide practical implications for improving teacher management practices in co-curricular programs.